Nursing and midwifery management of hypoglycaemia in healthy term neonates - Hewitt, Vivien; Watts, Robin; Robertson, Jeanette; Haddow, Gaby (The Joanna Briggs Institute, 2005)
The objective of this systematic review was to determine the best available evidence for maintenance of euglycaemia in healthy full-term neonates, and the management of asymptomatic hypoglycaemia in otherwise healthy full-term neonates. This review updates the World Health Organization's 1997 literature review which comprehensively addressed aspects such as the glucose homeostasis and metabolic adaptation at birth, effects of hypoglycaemia on the central nervous system, definition of hypoglycaemia, screening, prevention and treatment. In identifying areas of primary research that need to be undertaken, the World Health Organization (1997) noted that only a few studies of breast-fed babies had been undertaken up to that time.At birth the newborn infant must make significant adaptations from the in utero environment to the outside world. Failures of metabolic adaptation are most commonly manifested as hypoglycaemia. If unrecognised severe hypoglycaemia can lead to death,and the effects on long term mental and neurodevelopmental outcomes are not clear. ?Normal ranges? of blood glucose values have yet to be decisively defined, aspects of management remain controversial and a number of related research questions are still to be addressed.The availability of point-of-care and micro-sampling techniques to detect ?low? blood glucose levels and an increasingly litigious society have resulted in a definition for hypoglycaemia that is considerably higher than that postulated by Hartmann & Jaudon in 1937. Concern has been expressed that setting an unnecessarily high blood glucose level may result in needless trauma and cost. The administration of intravenous glucose to otherwise healthy newborn infants in the NICU may result in unnecessary pain to the neonate, emotional trauma to parents, increased cost to the hospital, and separation of the newborn infant at a crucial time in the bonding/breastfeeding process.